Responsabilidade pessoal do agente público por dano decorrente de violação a direito fundamental do cidadão: uma contribuição para o resgate da legalidade na atividade estatal - Oliveira, Joyce Chagas de (2014)
The paper conducts a study on the civil liability of the State in Brazil, that, after the Federal Constitution of 1988, adopted the theory of the administrative risk, in which the Public Administration will be responsible for the damages caused to individuals by their agents regardless of malice or fault, as stipulated in Article 37, §6th of the Constitution. In the first part, two basic concepts are highlighted: the fundamental taxpayer rights and the full binding of the Tax Administration, analyzing the daily tax activity that, often aiming for a higher tax levy, commits the so called politics sanctions, which are clear violations of the fundamental taxpayer rights. In the following, it is analyzed the compensable damages in the relation Fisctaxpayer, who are the public agents that can cause a tax damage and the need for a paradigm change: personal responsibility of the fiscal agent. It is studied the tax relation, already worn with the aim of reducing the existing tension and create a mechanism to make it more compatible with the legal system, with more equality between the parts (State and individual), surpassing the prejudice that exists today that every taxpayer is tax evader and every fiscal agent is arbitrary. Based on these assumptions, it is built a thought about the possibility of personally blame the public agent who caused the damage to the citizen as a way to rescue the effectiveness of the principle of legality, to seek punishment of who caused the damage, to decrease the tension in the relationship Fisc-taxpayer and thus to restore confidence in the State. The paper also broaches the educational and preventive role of the personal responsibility of the fiscal agent and, at the end, it discusses the procedural aspects of the subject.